2018
DOI: 10.5935/abc.20180156
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Family Enrollment in a Genetic Cascade Screening Program for Familial Hypercholesterolemia

Abstract: BackgroundGenetic cascade screening is the most cost-effective method for the identification of individuals with familial hypercholesterolemia (FH), but the best strategies for the enrollment of at-risk individuals in a FH screening program are not fully known.ObjectiveThe aim of this study is to identify the best predictors of familial enrollment into genetic screening, using features derived from tested probands.MethodsOne hundred and eighty-three index-cases (ICs) with a positive genetic result that had rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…In a previous publication, the authors reported that their FH cascade screening program could predict family enrollment based on IC features, useful information for devising better and more effective screening approaches for at-risk individuals. 10 However, there is an important gap in risk perception, cholesterol management, and other aspects related to FH. 11 The strategy of target screening in small cities can be effective, but some issues must be taken into account before choosing the city to screen.…”
Section: Diseases Inbornmentioning
confidence: 99%
“…In a previous publication, the authors reported that their FH cascade screening program could predict family enrollment based on IC features, useful information for devising better and more effective screening approaches for at-risk individuals. 10 However, there is an important gap in risk perception, cholesterol management, and other aspects related to FH. 11 The strategy of target screening in small cities can be effective, but some issues must be taken into account before choosing the city to screen.…”
Section: Diseases Inbornmentioning
confidence: 99%
“…Todas las muestras se analizaron mediante MLPA (Multiple Ligation-depend Probe Amplification) (MRC-Holland) para determinar la variación del número de copias 15 . La interpretación y clasificación de las variantes se estudiaron siguiendo las recomendaciones del consenso de la Asociación de Patología Molecular y del Colegio Médico Americano de Genética y Genoma (ACMG).…”
Section: Análisis Molecularunclassified
“…Silva-Souza, et al, 12 in the article entitled Predictors of Family Recruitment in a Program of Genetic Cascade Screening for Familial Hypercholesterolemia identified the best predictors of genetic family screening, using characteristics derived from their probands. 12 From January 2011 to July 2015, 183 probands (confirmed for FH by genetic testing) had their 1 st degree family members recruited for the cascade program. The response variable was the number of relatives that adhered to the recruitment.…”
mentioning
confidence: 99%